Peningkatan Prestasi Belajar Siswa untuk Materi Energi dengan Menggunakan Media “Mention and Get” - Mujiani, Dwi Safitri; Dermawan, Deden Dicky (AS-SABIQUN, 2023)
Teacher have to determine source of learning correctly so that he or she can manage student activity and the items of materials to be given better. Source of learning is object reference and or materials utilized for the activity of learning such as media printing and electronic, guest teacher, and also physical environment like nature, cultural and social. Relate to the mentioned, on academic year 2022 / 2023 one of the source of learning which is used for Science lesson in al muslim Bekasi is Science book arranged by al muslim Surabaya. There are some constraint faced in study of Science when using this book, for example : the items which many and enough heavily, while number of hours Iesson of Science in al muslim Bekasi only 4 hours in week. Besides, less available time which enough for a lesson teacher to draw up materials or appliances to test-drive in verification activity. Finally, in learning and teaching process the result is not maximal. Activity of review (lesson items) usually make bored student, because review only through oral questions. Therefore, designed a media of game " Mention and Get" used as variation of review activity in science learning, specially for the items of energi. Its result, by using media of game " Mention and Get" student learn evaluation can increase mount 20 %, from 64 % (first condition) becoming 84 % the result of final tes. Besides, from student observation also show the make-up of student motivation, from 70 % at first siclus become 90 % at second siclus and 97 % at third ciclus. While teacher performance aspect show " Good” category which increase from 76 % at first ciclus, becoming 84 % at second ciclus and 92 % at third ciclus. From the result, can be concluded that usage of media of game " Mention and Get" can improve student learn evaluation for the items of Energi, at science Iesson in class III Imam Syafi'i of al muslim elementary school Bekasi.